Pengaruh Beban Kerja Dan Stres Kerja Terhadap Kinerja Karyawan Pada CV. Sumber Harta Laut Mas Ambon - Wa Yuyun; Elsina H Aponno; Maria Marlyn Tetelepta (Jurnal Administrasi Terapan, 2024)
Based on the initial survey on CV. Sumber Harta Laut Mas Ambon shows that there are indications of workload problems on employees. On the other hand, it also shows symptoms of work stress so that it has an impact on employee performance. This study aims to determine how the effect of workload and work stress on employee performance at CV. Sumber Harta Laut Mas Ambon.The analytical method used in this study is descriptive analysis and multiple linear regression analysis. Descriptive analysis shows that the workload on employees of CV. Sumber Harta Laut Mas Ambon with an average value of 3.70 which is interpreted as high, while stressaverage work value of 3.02 which is also interpreted as high. The results of the regression analysis show that workload has a negative and significant effect on the performance of CV. Sumber Harta Laut Mas Ambon, work stress has a negative and significant impact on the performance of employees. CV. Sumber Harta Laut Mas Ambon And simultaneously workload and work stress have a significant effect on employee performance.Based on the results of this study, it can be concluded that the higher the workload and work stress, the lower the employee's performance. To overcome this, CV. Sumber Harta Laut Mas Ambon must try to reduce workload by paying attention to working conditions, and use of working time and targets to be achieved. Employee stress levels must also be reduced by paying attention to symptoms of employee stress on psychological, physical and behavioral indicators so that employee performance increases. Keywords: Workload, Work Stress, Employee Performance.